2023
DOI: 10.3389/fimmu.2023.1117310
|View full text |Cite
|
Sign up to set email alerts
|

LDC7559 inhibits microglial activation and GSDMD-dependent pyroptosis after subarachnoid hemorrhage

Abstract: Mounting evidence indicates that inhibition of microglial activation and neuronal pyroptosis plays important roles in brain function recovery after subarachnoid hemorrhage (SAH). LDC7559 is a newly discovered gasdermin D (GSDMD) inhibitor. Previous studies have demonstrated that LDC7559 could inhibit microglial proliferation and pyroptosis. However, the beneficial effects of LDC7559 on SAH remain obscure. Based on this background, we investigated the potential role and the mechanism of LDC7559 on SAH-induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Upregulation of phosphorylated TAK1 promotes NF-κB p65 nuclear translocation and NLRP3 upregulation, inducing neuronal pyroptosis [64]. Additionally, LDC7559, a novel GSDMD inhibitor, inhibited neuronal pyroptosis post-SAH [65]. However, several studies have reported mechanisms underlying NLRP3-mediated microglial pyroptosis in SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of phosphorylated TAK1 promotes NF-κB p65 nuclear translocation and NLRP3 upregulation, inducing neuronal pyroptosis [64]. Additionally, LDC7559, a novel GSDMD inhibitor, inhibited neuronal pyroptosis post-SAH [65]. However, several studies have reported mechanisms underlying NLRP3-mediated microglial pyroptosis in SAH.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 and caspase inhibitors have been explored for the treatment of neurodegenerative diseases by targeting overactivated pyroptosis and have shown certain effects ( 44 , 118 , 119 ). Recently, LDC7559, a newly developed selective GSDMD inhibitor, was reported to promote brain functional recovery by inhibiting over-activated pyroptosis by directly blocking the GSDMD-N-terminus ( 120 , 121 ). However, whether these inhibitors may also be used for cancer treatment remains to be investigated.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%